Il problema interpretativo di Gerard nel dibattito sul gusto nel Settecento inglese (Itinera, 2013)
The chronological proximity of the publication of Gerard’s and Hume’s aesthetic essays gives rise to a delicate question of interpretation which casts doubt on Gerard’s influence on his master. This paper will demonstrate how their different concepts of taste (the former still talking about “faculties”, the latter about “sentiment”) and, consequently, the role of judgment justify the hypothesis that Gerard did not affect Hume’s theory of aesthetic evaluation.